Visual outcome and early complications of sutureless and glueless scleral fixated intraocular lens - Agarwal, Lalit; Agarwal, Nisha; Gurung, Rajya Laxmi; Chaubey, Rahul; Jha, Bhaskar Kumar; Chaudhary, Bishwa Pratap (Nepalese Journal of Ophthalmology, 2016)
Introduction: In the absence of capsular support, anterior chamber intraocular lens (IOL), iris fixated IOL and sutured scleral fixated intraocular lens (SFIOL) implantation have been performed for many years. Recently sutureless glued SFIOL have been used as a primary or secondary procedure to correct aphakia. In this study we have used sutureless and glueless technique of SFIOL implantation. Methodology: An interventional case series was conducted. Aphakic patients without capsular support, sub-luxated lens (>180°), dislocated lens and dislocated IOL were the inclusion criteria. The patients with hazy cornea, non-dilating pupil, macular scar and glaucoma were not enrolled in the study. Results: Of 62 eyes who completed 1 month follow- up, 48 were men and 14 women. There was a significant improvement in uncorrected distance visual acuity after surgery (p